2021
DOI: 10.1128/spectrum.01330-21
|View full text |Cite
|
Sign up to set email alerts
|

Testing Denmark: a Danish Nationwide Surveillance Study of COVID-19

Abstract: To date, including 318,522 participants, this is the largest population-based study with broad national participation where tests and questionnaires have been sent to participants’ homes. We found that more emphasis from national and local authorities toward the risk of infection should be placed on age of tested individuals, type of occupation, as well as exposure in local communities and households.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
6
16
0
Order By: Relevance
“…Elevated infection risk in occupational groups with limited ability to work from home and those involving exposure to patients and/or the public echoes findings from the previous studies with more limited adjustment for potential confounding and from other global regions 1 2 3 4 5 12 13 . Across all analyses in the current study, adjustment for sociodemographic and health-related factors and non-work activities had limited impact on estimates.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Elevated infection risk in occupational groups with limited ability to work from home and those involving exposure to patients and/or the public echoes findings from the previous studies with more limited adjustment for potential confounding and from other global regions 1 2 3 4 5 12 13 . Across all analyses in the current study, adjustment for sociodemographic and health-related factors and non-work activities had limited impact on estimates.…”
Section: Discussionsupporting
confidence: 60%
“…Notable occupational inequalities in infection risk have emerged during the Coronavirus Disease 2019 (COVID-19) pandemic. Research and surveillance data across various global regions have repeatedly indicated elevated risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in workers in various essential and/or public-facing industries, such as health and social care, transportation, education, and cleaning and service occupations 1 2 3 4 5 compared to other workers or the adult population. Occupational differences in the ability to work from home, the frequency and intensity of workplace exposure to other people, environmental features of the workspace, and the implementation of infection control procedures plausibly contribute to differential risk of infection and transmission at work 6 7 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite a high level of adherence to national recommendations (see Fig. S1 in the supplemental material), no discernible difference was found between individual protective health measures and serostatus, as seen in earlier studies ( 17 , 21 ), but no adherence to all of the measures was significantly associated with seropositivity. Several studies have reported low usage of face masks in DCS.…”
Section: Discussionmentioning
confidence: 63%
“…This study provides information about infection and immunity to COVID-19 among employees working in DCS in Denmark as part of the national large-scale epidemiological surveillance study, Testing Denmark ( 17 ). We used a point-of-care rapid antibody test (POCT), identifying previous infection by detecting IgM or IgG against the virus spike protein, allowing an estimate of the seroprevalence along with risk factors and behavior among DCS staff.…”
Section: Introductionmentioning
confidence: 99%
“…In working-age adults, the workplace is a persistent and notable source of potential SARS-CoV-2 exposure (3)(4)(5)(6), with considerable variation across occupational groups. Occupations that cannot be completed from home and involve high levels of contact with others -such as healthcare, teaching, public transport and personal service occupations -are associated with elevated infection risk in studies across a range of global regions (3,(7)(8)(9)(10)(11)(12)(13)(14). Differential vaccine uptake in high-exposure occupations is an area of concern, particularly for workers with conditions that render them vulnerable to severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%